Village Financial Management StrategyLombok Timur District (Case Study In Keruak District) - Syaefullah; Marzuki (Yayasan Hisnul Muslim Lombok, 2024)
One of the positive impacts of regional autonomy is the change in the government system from a centralized system to a decentralized system. Decentralization in regional autonomy means that there is a delegation of authority from the central government to regional governments. The delegation of authority means the granting of authority and flexibility to the regions to manage and utilize regional resources optimally. Although the emphasis on autonomy is placed at the Regency/City level, in essence, independence must start from the lowest level of government, namely the Village. Because government starts from the village, as a follow-up to the provisions contained in Law Number 23 of 2014 concerning Regional Government, Law Number 6 of 2014 concerning Villages was issued. Article 1 of Law Number 6 of 214 concerning Villages states that: